2022
DOI: 10.1126/sciadv.abm9825
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy in eight European countries: Prevalence, determinants, and heterogeneity

Abstract: We examine heterogeneity in COVID-19 vaccine hesitancy across eight European countries. We reveal striking differences across countries, ranging from 6.4% of adults in Spain to 61.8% in Bulgaria reporting being hesitant. We experimentally assess the effectiveness of different messages designed to reduce COVID-19 vaccine hesitancy. Receiving messages emphasizing either the medical benefits or the hedonistic benefits of vaccination significantly increases COVID-19 vaccination willingness in Germany, whereas high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 70 publications
(102 reference statements)
6
72
1
Order By: Relevance
“…This misperception may indicate a false consensus bias: the tendency to assume that others are similar to oneself. Using different data sources, we replicated the finding of an underestimation in vaccine acceptance for different populations and across different time periods ( 11 , 60 ), thus generalizing our findings beyond the local context of Rome.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This misperception may indicate a false consensus bias: the tendency to assume that others are similar to oneself. Using different data sources, we replicated the finding of an underestimation in vaccine acceptance for different populations and across different time periods ( 11 , 60 ), thus generalizing our findings beyond the local context of Rome.…”
Section: Discussionsupporting
confidence: 73%
“…As a second comparison, we used the Periscope survey ( 11 ), which contains information about vaccine acceptance and empirical expectations in Bulgaria, France, Italy, Poland, Spain, and Sweden between June 14 and June 25, 2021, a period that overlaps with the first two waves of our survey. Calculating the misperception in empirical expectations for these countries, we find significant misperceptions for all countries (See Fig.…”
Section: Study 1: Diagnosis Of the Vaccination Norm Over Timementioning
confidence: 99%
See 1 more Smart Citation
“…Higher levels of vaccination hesitancy in Eastern European countries, particularly in Russia and Bulgaria may be particularly relevant. [24][25][26][27] Steinert et al 28 found no adequate response to messages about the benefits of vaccination in several countries including Bulgaria and Poland, which was not the case in Germany and the UK.…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) vaccination campaigns in Europe were launched at the beginning of 2021 and were met with varying levels of vaccine hesitancy. [1][2][3] Nevertheless, by the end of the year, 69% of the population in the European Economy Area (EEA) completed the initial vaccination protocol consisting of two doses of BNT162b2 (BioNTech/Pfizer, mRNA-1273 (Moderna) or AZD1222 (Oxford/AstraZeneca), or a single dose of AD26.COV2.S (Janssen/ Johnson & Johnson). 4 Although the use of particular vaccines in the EEA varied, while the vaccination protocols (e.g., regarding a gap between doses) were subject to temporal changes depending on vaccine availability in selected countries, the BNT162b2 was the most often administrated product in the EEA countries.…”
Section: Introductionmentioning
confidence: 99%